Structurally-functional features of left ventricular myocardium and endothelial dysfunction in rheumatoid arthritis depending on presence of hypertension - E E Myasoedova; S E Myasoedova; M G Omeljanenko; S. V. Objerina (Научно-практическая ревматология)
Objective. To study the structure and functional peculiarities of left-ventricular myocardium and endothelial dysfunction in rheumatoid arthritis (RA) in connection with the course of disease, concomitant arterial hypertension (AH) and cardiovascular risk factors. Material and methods. Before the beginning of regular antihypertensive therapy we observed 55 pts with RA, 30 of them had mild or moderate AH developed in the course of RA and 36 pts with essential hypertension (EH) without rheumatic diseases. Wfe evaluated anamnesis, blood pressure level (BPL), echocardiography data, endothelial vasodilation capacity and endothelial dysfunction index. All pts were purely comparable in age; RA with AH pts and EH pts — in BPL, anamnesis duration, SCORE-risk. No one of the observed persons had associated clinical states. 26 healthy subjects made control group. Results. RA with AH pts in comparison with EH had marked left-ventricular hypertrophy. Concentric hypertrophy prevailed in RA. 65,3% of RA-pts had diastolic dysfunction type 1. Endothelial dysfunction in RA-pts was found more often (in 57,9% individuals with RA and normal BPL and in 50% pts with RA and concomitant AH) (p<0,05) than in EH-pts (20%). Thus, left-ventricular hypertrophy in RA optionally depended on AH presence but it is closely connected with metabolic (hyperlipidemia, abdominal obesity) and endocrine (menopause) disorders in pts with chronic autoimmune inflammation.